2006
DOI: 10.1007/s10697-006-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of the stabilization of a supersonic flat-plate boundary layer by a porous coating

Abstract: On the basis of a numerical solution of the two-dimensional Navier-Stokes equations, the stability and the receptivity of a supersonic (M ∞ = 6) boundary layer on a flat plate with a passive porous coating partially absorbing flow disturbances is studied. The results of direct numerical simulation are in good agreement with the data of the linear stability theory. The studies confirm the possibility of effectively stabilizing the second mode of the supersonic boundary layer using porous coatings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…It was found that bluntness tended to stabilize the boundary layer. These results were consistent with the theoretical analyses of Fedorov [10] and the numerical results of Egorov et al [16,17]. Wang and Zhong [22] numerically investigated the steady base flow and the receptivity of the hypersonic boundary layer corresponding to Maslov et al's [9] leading-edge receptivity experiments.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…It was found that bluntness tended to stabilize the boundary layer. These results were consistent with the theoretical analyses of Fedorov [10] and the numerical results of Egorov et al [16,17]. Wang and Zhong [22] numerically investigated the steady base flow and the receptivity of the hypersonic boundary layer corresponding to Maslov et al's [9] leading-edge receptivity experiments.…”
Section: Introductionsupporting
confidence: 83%
“…Such results were consistent with the theoretical analysis of Fedorov and Khokhlov [3,4]. Egorov et al [16] numerically solved unsteady twodimensional flows relevant to the receptivity of the supersonic and hypersonic boundary layers using a second-order total-variationdiminishing (TVD) scheme. To compare with numerical simulation results, theoretical analyses were carried out by the conventional linear stability theory (LST) and the LST including nonparallel flow effects.…”
Section: Introductionsupporting
confidence: 80%
“…It was found that there was a good agreement between normal-mode amplitudes calculated with the help of the theoretical receptivity model and those obtained from projecting the numerical results onto the normal modes. Egorov et al 26 studied stability and receptivity of a Mach 6 flow over a flat plate with a porous coating by numerically solving two-dimensional Navier-Stokes equations. Their numerical results were in a good agreement with theoretical analysis based on LST.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that there was a good agreement between normal-mode amplitudes calculated with the help of the theoretical receptivity model and those obtained by projecting the numerical results onto the normal modes. Egorov et al [43] studied the stability and receptivity of a Mach 6 flow on a flat plate with a porous coating by numerically solving the two-dimensional Navier-Stokes equations. Their numerical results were in good agreement with the theoretical analysis based on LST.…”
Section: Introductionmentioning
confidence: 99%